The Perceived Benefits and Barriers to Summer Meal Participation in New York City. - Kannam, Allison V. (Tufts Archival Research Center, 2018)
Only 15 percent of U.S. children who receive free and reduced-price lunches during the year access USDA-sponsored free summer meal programs when school is out of session. Previous research has explored parent perceptions of summer meals to understand the underutilization of the program. The present study examined the role that summer meals have in shaping parents’ experiences providing food and children’s experiences eating in the summer with regard to the perceived benefits and barriers to participation. Twenty qualitative semi-structured phone interviews were conducted with parents from Queens, Bronx, and Brooklyn, New York, including both participants and non-participants in summer meals. All interview respondents were recruited through their participation in a separate summer meals survey at their child’s elementary school, where they offered their contact information for follow-up. The interview asked questions about the challenges that parents face providing food in the summer and the perceived benefits or barriers to participating in a free meals program. Interviews were transcribed, coded, and analyzed thematically. Results demonstrated that summer meals reduce financial and psychological stress for parents, foster social support and connections within the community, and improve consumption habits for children. However, awareness of meal programs remains low and some programs may lack cultural inclusivity, preventing families with religious dietary restrictions from participating. On the whole, while the main purpose of summer meals is to reduce food insecurity, the programs provide many additional social and psychological benefits that demonstrate their value to low-income families. Summer meal administrators should incorporate messaging about these advantages into their marketing to leverage support for and participation in the programs, while meal sites should continue innovating ways to improve access to meals for all families.